Collegiality versus managerialism. Management of Polish public universities in the higher education system under reform - Urbanek, Piotr (Kolegialność versus menedżeryzm. Zarządzanie uczelnią publiczną w reformowanym systemie szkolnictwa wyższego w Polsce, 2020)
The reform of the Polish higher education system introduces an alternative model of university management, referring to the idea of managerialism. The strong academic leaders, limiting the role of academic collegiate bodies, and the involvement of external stakeholders in university management are the pillars of the new model. The article attempts to assess the changes in the structures of university authorities introduced in Polish universities as a result of the reform. The study was conducted based on an analysis of the statutes of 18 public universities. The obtained results indicate two regularities. Firstly, the new solutions place the university system closer to a model based on managerial logic. Secondly, the changes in university authority structures are not accompanied by the professionalization of management processes. Universities that maintained traditional academic authority structures before the reform made more extensive use of business management methods
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 171-180
Keywords: public universities; collegiality; managerialism; reform of the higher education system; uczelnie publiczne; kolegialność; menedżeryzm; reforma systemu szkolnictwa wyższego